Conformation and Stability of the a-Helical Intermediate of Intact and Thiol-modified b-Lactoglobulin Induced by Sodium Dodecyl Sulfate - CHAMANI, J. (Asian Journal of Chemistry, 2010)
β-Lactoglobulin is a predominantly β-sheet protein, although it has a markedly high intrinsic preference for α-helical structure. β-Lactoglobulin assumes a monomeric native conformation at acidic condition. It has a free thiol at Cys 121, which is buried between the β-barrel and the C-terminal major α-helix. This thiol group was specifically reacted with 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) at pH 2, producing a modified β-lactoglobulin (TNB-β-LG) containing a mixed disulfide bond with 5-thio-2-nitrobenzoic acid. The formation of non-native α-helical intermediate of intact and thiol modified β-lactoglobulin was induced by sodium dodecyl sulfate. The conformation and stability of non-native α-helical intermediate (αI) state of TNB-β-LG were studied by circular dichroism and fluorescence techniques. The effect of sodium dodecyl sulfate on the structure of αI state at acidic condition was utilized to investigate the contribution by hydrophobic interactions to the stability of αI intermediate. The present results suggest that modification of the buried thiol group destabilizes the rigid hydrophobic core, producing a monomeric state that is nativelike at pH 2. Therefore TNB-β-LG will become a useful model to analyze the conformation and stability of the intermediate of protein folding.